Reading Lena Dunham’s Girls
XI, 255 p. 3 illus. in color.
Keywords: In this book, leading international and emerging scholars consider the mixed critical responses to Lena Dunham’s TV series Girls and reflect on its significance to contemporary debates about postfeminist popular cultures in a post-recession context. The series features both familiar and innovative depictions of young women and men in contemporary America that invites comparisons withSex and the City. It aims for a refreshed, authentic expression of postfeminist femininity that eschews the glamour and aspirational fantasies spawned by its predecessor. The authors of this volume discuss the contemporary scholarship on Girls, from its representation of post-millennial gender politics to revulsion and repugnance at depictions of the messiness and imperfections of sex, embodiment, and social interactions. Topics covered by the chapters include Dunham’s privileged role as author/auteur/actor, sexuality, body consciousness, millennial gender identities, the politics of representation, neoliberalism, and post-recession society. This book provides diverse and provocative critical responses to the show and to wider social and media contexts, and contributes to a new generation of feminist scholarship with a powerful concluding reflection from Rosalind Gill. This work will appeal to those interested in feminist theory, identity politics, popular culture, and media.